Skin volatile organic compound emissions from 14 healthy young adults under controlled conditions. (15th August 2022) - Zou, Ziwei; Yang, Xudong
Abstract: The human skin is an important source of volatile organic compounds (VOCs) in indoor environments. In this study, VOC emissions from whole-body skin of 14 healthy young adults were measured using a specially designed environmental chamber under controlled conditions. The number of VOC species in whole-body skin emissions ranged from 38 to 69 and the total emission rate of all VOCs detected in whole-body skin emissions ranged from 164 to 518 μg/h. The similarities of VOC species among different subjects were more prominent, while the emission rate of the same VOC among different subjects varied significantly. In particular, eight VOCs (acetone, 6-methyl-5-hepten-2-one (6-MHO), geranylacetone, hexanal, heptanal, octanal, nonanal, and decanal) were emitted from the skin of all subjects, most likely originating due to the reaction of ozone with human skin. These VOCs accounted for a relatively large proportion of the total emission rate, indicating that the reaction of skin with ozone was an important source for skin VOC emissions. In addition, siloxanes, aldehydes, ketones, and alcohols contributed remarkably to whole-body skin emission rates. Overall, this study showed information on the apportionments of VOC species and emission rates of whole-body skin emissions, which shed more light on the emission characteristics of human skin as a VOC source. Highlights: VOC species and emission rates of whole-body skin from 14 subjects were determined. Eight VOCs (skin ozonolysis products) were emitted from the skin of all subjects. VOC emission rates were significantly different among the subjects.